2022
DOI: 10.1155/2022/1516668
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Retinal Microcirculation in Diabetic Patients Using Adaptive Optics Ophthalmoscopy and Optical Coherence Angiography

Abstract: The current research approaches the retinal microvasculature of healthy volunteers (17 subjects), patients with diabetes mellitus without retinopathy (19 subjects), and of diabetic patients with nonproliferative (17 subjects) and proliferative (21 subjects) diabetic retinopathy, by using adaptive optics ophthalmoscopy and optical coherence ophthalmoscopy angiography. For each imaging technique, several vascular parameters have been calculated in order to achieve a comparative analysis of these imaging biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…The current study proves once more the appearance of structural alterations seen in retinal arterioles of diabetic patients, mirrorred by WT, WLR and WCSA parameters. An increased WLR in patients with diabetic retinopathy has been reported in previous studies describing arteriolar remodeling (5,6). The process itself may appear due to muscle hypertrophy and fibrosis and is best reflected by WLR (7,8).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The current study proves once more the appearance of structural alterations seen in retinal arterioles of diabetic patients, mirrorred by WT, WLR and WCSA parameters. An increased WLR in patients with diabetic retinopathy has been reported in previous studies describing arteriolar remodeling (5,6). The process itself may appear due to muscle hypertrophy and fibrosis and is best reflected by WLR (7,8).…”
Section: Discussionmentioning
confidence: 64%
“…Retinal vessels geometry, including measurements of vessel branching angles, branching complexity, tortuosity, length-todiameter ratio and fractals comprehend another 1 Clinical Emergency Eye Hospital, Bucharest, Romania 2 Department of Ophthalmology, "Ovidius" University of Medicine, Constanța, Romania 3 Retina Clinic, Bucharest, Romania 4 "Carol Davila" University of Medicine and Pharmacy, Bucharest, Romania 5 Manchester Royal Eye Hospital, Manchester University Hospitals NHS Foundation Trust, Manchester, UK 6 County Clinical Emergency Hospital of Constanta, Romania group of retinal vessel-linked biomarkers (2). For example, a decreased fractal dimension has been shown to be associated with diabetic retinopathy (3).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating the utility of AOI for DR have also observed significant changes in WLR. Recent studies comparing DR groups to control have reported an increase in WLR, 7,11,28,29 retinal arteriole structural alterations, 28 an increase in perifoveal capillary diameters, 7 and a decrease in blood flow within retinal vessels. 29 When comparing type 1 and type 2 diabetes, no significant differences were observed in the context of WLR.…”
Section: Discussionmentioning
confidence: 99%
“…Пристрої з АО дозволяють виявити ранні явища ремоделювання артеріол сітківки у пацієнтів із цукровим діабетом (ЦД), у тому числі за відсутності ознак діабетичної ретинопатії (ДР). Так, було виявлено, що товщина судинної стінки та показники співвідношення W/L у пацієнтів із цукровим діабетом без ДР вищі, ніж у здорових осіб [32,34,38]. Таким чином, значення товщини стінки артеріол сітківки та показники співвідношення W/L можна розглядати як ранні біомаркери мікроангіопатії у пацієнтів з ЦД.…”
Section: ключові словаunclassified
“…Ці показники були вищими у порівнянні з відповідними у контрольних групах (від 0,22 до 0,27) у здорових осіб. Очікувано найвищі значення співвідношення W/L були виявлені у пацієнтів з проліферативною стадією ДР [36,38].…”
Section: таблиця 2 морфометричні показники судин сітківки у пацієнтів...unclassified